Colossal permittivity and humidity sensing properties of CaCu3Ti4O12 ceramics derived from cockle shell CaCO3 via CO2 absorption - Kaniknun Sreejivungsa; Suppanat Kosolwattana; Morakot Sakulsombat; Prasit Thongbai (Scientific Reports)
Abstract Cockle shells served as a sustainable and non-toxic calcium source for CO2 capture through carbonation–calcination cycles. In this study, CaCO3 derived from cockle shells was used to synthesize CaCu3Ti4O12 (CCTO) ceramics via the solid-state reaction method and sintered at 1010–1090 °C. The resulting ceramics exhibited colossal dielectric permittivity (∼ 105 at 1 kHz, 25 °C) and a low dielectric loss (tanδ ≈ 0.04), confirming their suitability for capacitor applications. The high dielectric permittivity was primarily attributed to the internal barrier layer capacitor mechanism, in which insulating grain boundaries separated semiconducting grains, enhancing interfacial polarization. Impedance spectroscopy supported this explanation, while DC bias-dependent dielectric measurements revealed a noticeable decrease in permittivity under applied voltage, indicating that surface barrier layer capacitor effects at the ceramic–electrode interface also contributed to the dielectric behavior. Furthermore, X-ray photoelectron spectroscopy confirmed the presence of oxygen vacancies and hydroxyl groups at the ceramic surface, which facilitated water molecule adsorption and modulated interfacial charge transport. As a result, the CCTO ceramics demonstrated excellent humidity sensing performance, with a fast response time of 0.25 min, a recovery time of 0.45 min, and a low hysteresis error of 2.3%. These findings demonstrate the dual role of cockle shell-derived CaCO3 as both a sustainable CO2 sorbent and a valuable precursor for high-performance dielectric and humidity-sensing ceramics.